2020
DOI: 10.26650/iuitfd.2019.0080
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidity and Sleep Problems in Children and Adolescents With Attention Deficit Hyperactivity Disorder in Relation to Attention Deficit Hyperactivity Disorder Presentation, Age and Gender

Abstract: Bu çalışmada, DEHB tanılı çocuk ve ergenlerden oluşan klinik bir örneklemde psikiyatrik komorbidite, uyku problemleri ve bunların DEHB görünümü, yaş ve cinsiyetle olan ilişkilerinin incelenmesi amaçlanmış. Gereç ve Yöntem: Çalışmaya 6-17 yaş arası 154 katılımcı dahil edildi. Psikiyatrik bozuklukları değerlendirmek amacıyla yarı yapılandırılmış bir klinik görüşme gerçekleştirildi. İçselleştirme ve uyku sorunlarını değerlendirmek için Çocuklar için Anksiyete Bozuklukları Tarama Ölçeği (ÇATÖ), Çocuk Depresyon Env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Seventeen studies investigated the prevalence of social anxiety in adolescents and adults with ADHD. Of these, only three studies were conducted with adolescents ( Coskun et al, 2020 ; Marmorstein, 2007 ; Yüce et al, 2013 ), the rest with adults. Studies that investigated diagnostic SAD in adolescents and adults with diagnostic ADHD (in clinical samples) reported prevalence rates of .04% ( Secnik et al, 2005 ), 3.3% ( Pehlivanidis et al, 2020 ), 9% ( O’Rourke et al, 2020 ), 14.2% ( Anker et al, 2018 ), 14.66% ( Coskun et al, 2020 ), 20% ( Wilens et al, 2005 ), 31% ( Rucklidge et al, 2016 ), 34.2% ( Yüce et al, 2013 ), 38.2% ( Gorlin et al, 2016 ), 39.7% ( Edel et al, 2010 ), and 46.7% ( Moore et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen studies investigated the prevalence of social anxiety in adolescents and adults with ADHD. Of these, only three studies were conducted with adolescents ( Coskun et al, 2020 ; Marmorstein, 2007 ; Yüce et al, 2013 ), the rest with adults. Studies that investigated diagnostic SAD in adolescents and adults with diagnostic ADHD (in clinical samples) reported prevalence rates of .04% ( Secnik et al, 2005 ), 3.3% ( Pehlivanidis et al, 2020 ), 9% ( O’Rourke et al, 2020 ), 14.2% ( Anker et al, 2018 ), 14.66% ( Coskun et al, 2020 ), 20% ( Wilens et al, 2005 ), 31% ( Rucklidge et al, 2016 ), 34.2% ( Yüce et al, 2013 ), 38.2% ( Gorlin et al, 2016 ), 39.7% ( Edel et al, 2010 ), and 46.7% ( Moore et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, only three studies were conducted with adolescents ( Coskun et al, 2020 ; Marmorstein, 2007 ; Yüce et al, 2013 ), the rest with adults. Studies that investigated diagnostic SAD in adolescents and adults with diagnostic ADHD (in clinical samples) reported prevalence rates of .04% ( Secnik et al, 2005 ), 3.3% ( Pehlivanidis et al, 2020 ), 9% ( O’Rourke et al, 2020 ), 14.2% ( Anker et al, 2018 ), 14.66% ( Coskun et al, 2020 ), 20% ( Wilens et al, 2005 ), 31% ( Rucklidge et al, 2016 ), 34.2% ( Yüce et al, 2013 ), 38.2% ( Gorlin et al, 2016 ), 39.7% ( Edel et al, 2010 ), and 46.7% ( Moore et al, 2016 ). Studies that investigated diagnostic SAD in adults with subdiagnostic ADHD reported prevalence rates of 2.9% (community sample: Park et al, 2011 ) and 30% (incarcerated adults: Einarsson et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation